CAUSE AND EFFECT OF MIGRATION ON THE NIGERIAN ECONOMY - Okonjo Emmanuel Tobe (2019)
The need to review the role migration play in the Nigeria Economy is based on the fact that both the internal and international migrations in the country have experienced significant changes not only in the pattern of the process, but also on the cause and effect on the economic life of the nation. In order to appreciate the changes in the international migration, in particular, several available and relevant works on the topic were reviewed, including those on internal migration, which could have served as a precursor to the international migration. The literature review is also undertaken as a way of appreciating the gaps in knowledge on international migration, which would require refocusing and/or exploring migration.